(untitled) (FULafia Journal of Science and Technology, 2025)
The frictional properties of a material are useful in designing equipment for crop processing and storage. The effect of moisture content of two varieties of palm kernel and shell on the coefficient of sliding friction of a local fabric was determined. An oven drying method at 105 oC was used to determine the moisture content according to ASAE Standards. The moisture content of dura and tenera varieties were 17.4 and 18.2 % (w.b.) which were individually adjusted to 9, 13 and 17 % by adding 76.3, 39.8 and 3.3 g; and 82.3, 46.4 and 10.6 g distilled water respectively. The angle of repose apparatus was used to determine the coefficient of sliding friction of palm kernel and shell of dura and tenera varieties on the two faces of local fabric. The coefficient of sliding friction for dura kernel and shell on the two faces of a local fabric ranged from 0.384-0.655 for 9 %; 0.484-0.706 for 13 %; and 0.462-0.695 for 17 %. The coefficient of sliding friction for tenera kernel and shell on the two faces of a local fabric ranged from 0.660-0.947 for 9 %; 0.711-0.852 for 13 % and 0.611-0.902 for 17 %. The moisture contents of dura palm kernel, tenera palm kernel and tenera palm shell had significant effect (p<0.05) on the coefficient of sliding friction on face A and face B of the local fabric but moisture content of dura palm shell had no significant effect (p>0.05) on the coefficient of sliding friction.